Working with indigenous, local and scientific knowledge in assessments of nature and nature's linkages with people - Hill, Rosemary (2020)
Working with indigenous and local knowledge (ILK) is vital for inclusive assessments of nature and nature's linkages with people. Indigenous peoples’ concepts about what constitutes sustainability, for example, differ markedly from dominant sustainability discourses. The Intergovernmental Platform on Biodiversity and Ecosystems Services (IPBES) is promoting dialogue across different knowledge systems globally. In 2017, member states of IPBES adopted an ILK Approach including: procedures for assessments of nature and nature's linkages with people; a participatory mechanism; and institutional arrangements for including indigenous peoples and local communities. We present this Approach and analyse how it supports ILK in IPBES assessments through: respecting rights; supporting care and mutuality; strengthening communities and their knowledge systems; and supporting knowledge exchange. Customary institutions that ensure the integrity of ILK, effective empowering dialogues, and shared governance are among critical capacities that enable inclusion of diverse conceptualizations of sustainability in assessments.